tRNA Processing and Subcellular Trafficking Proteins Multitask in Pathways for Other RNAs - Hopper, Anita K.; Nostramo, Regina T. (Frontiers in Genetics, 2019)
This article focuses upon gene products that are involved in tRNA biology, with particular emphasis upon post-transcriptional RNA processing and nuclear-cytoplasmic subcellular trafficking. Rather than analyzing these proteins solely from a tRNA perspective, we explore the many overlapping functions of the processing enzymes and proteins involved in subcellular traffic. Remarkably, there are numerous examples of conserved gene products and RNP complexes involved in tRNA biology that multitask in a similar fashion in the production and/or subcellular trafficking of other RNAs, including small structured RNAs such as snRNA, snoRNA, 5S RNA, telomerase RNA, and SRP RNA as well as larger unstructured RNAs such as mRNAs and RNA-protein complexes such as ribosomes. Here we provide examples of steps in tRNA biology that are shared with other RNAs including those catalyzed by enzymes functioning in 5’ end-processing, pseudoU nucleoside modification, and intron splicing as well as steps regulated by proteins functioning in subcellular trafficking. Such multitasking highlights the clever mechanisms cells employ for maximizing their genomes.